Role of white matter hyperintensity in effects of apolipoprotein E on cognitive injury - Raber, Jacob; Silbert, Lisa C. (Frontiers in Human Neuroscience, 2023)
Magnetic Resonance Imaging (MRI) T2-weighted white matter hyperintensity (WMH) is a marker of small vessel cerebrovascular pathology and is of ischemic origin. The prevalence and severity of WMH is associated with cardiovascular risk factors, aging, and cognitive injury in mild cognitive impairment (MCI), vascular dementia, and Alzheimer’s disease (AD). WMH especially affects executive function, with additional effects on memory and global cognition. Apolipoprotein E (apoE) plays a role in cholesterol metabolism and neuronal repair after injury. Human and animal studies support a role for apoE in maintaining white matter integrity. In humans, there are three major human apoE isoforms, E2, E3, and E4. Human apoE isoforms differ in risk to develop AD and in association with WMH. In this Mini Review, we propose an increased focus on the role of WMH in cognitive health and cognitive injury and the likely role of apoE and apoE isoform in modulating these effects. We hypothesize that apoE and apoE isoforms play a role in modulating WMH via apoE isoform-dependent effects on oxylipins and 7-ketocholesterol, as well as amyloid related vascular injury, as seen in cerebral amyloid angiopathy.